Use of corticosteroid therapy on the modulation of uterine inflammatory response in mares after artificial insemination with frozen semen - Papa, Frederico Ozanam [UNESP]; Dell'aqua Junior, José Antônio [UNESP]; Alvarenga, Marco Antonio [UNESP]; Melo, Cely Marini [UNESP]; Zahn, Fabiola Soares [UNESP]; Lopes, Maria Denise [UNESP] (Hippiatrika Verlag Mbh, 2008)
In order to modulate uterine inflammatory response and evaluate the effect of corticosteroid therapy on fertility, 90 cycles of 45 mares were used for artificial insemination with frozen semen, using three different protocols: G1 - inseminated with frozen semen (800 x 10(6) viable spermatozoa pre-freezing) + 20 mL of seminal plasma; G2 - inseminated with frozen semen (800 x 10(6) viable spermatozoa pre-freezing) + corticosteroid therapy; G3 - inseminated with frozen semen (800 x 10(6) viable spermatozoa pre-freezing) + 20 mL of seminal plasma + corticosteroid therapy. Corticosteroid therapy consisted on one administration of prednisolone acetate (0.1 mg/Kg - Predef (R)) when mares presented 35mm follicles and uterine edema, concomitantly with the unique dose of hCG (human chorionic gonadotropin), then repeated each 12 hours until ovulation. on first fertility trial, with normal mares, there was no difference between control and treated groups (p>0.05), using seminal plasma associated with corticosteroid therapy (40 vs. 38%, respectively) or corticosteroid therapy alone (40 vs. 45% respectively). The second fertility trial, performed with mares with previous history of post-insemination endometritis, demonstrated a significant increase of pregnancy rate when mares were submitted to corticosteroid therapy (0.0 vs. 64.5%, respectively; p<0.05). Corticosteroid therapy was shown to be safe, with no physical or reproductive alterations on treated mares, demonstrating to be an adequate option to those animals with history of post-breeding or post-insemination endometritis. Further clinical research is necessary to confirm these results and contribute to the establishment of preventive therapy for cases of post-insemination endometritis.
Keywords: equine; corticosteroid; seminal plasma; frozen semen; fertility; reproduction